Effect of Water:Bean Ratio during Extraction Process on Solid, Protein, and Calcium Extractability and on Ratio of 7S/11S Protein Fraction - Yuwono, Sudarminto Setyo; Susanto, Tri (Jurnal Teknologi Pertanian, 2006)
Water: bean ratio has an important role during extraction process in tofu industries. This factor determines yield and textural properties of tofu. The aim of the research was to evaluate the role of water: bean ratio on soymilk characteristics and to determine the extractability of solids, protein, and calcium. It was shown that the increase amount of water, from water to bean ratio of 10:1 to 30:1, reduced the total solids, protein and calcium content of soymilk, however, increased the total extracted solids, protein and calcium in the range of 53,53% - 68,44%,Â  73,08% - 83,21%, and 23,38% - 38,44%, respectively. Such an increase also resulted in the increase of 7S/11S globulin ratio, from 0,232 to 0,259. Â  Key words: soybean, water:bean ratio, globulin 7S/11S